Proyek Penguatan Profil Pelajar Pancasila dalam Membangun Kreativitas Siswa Sekolah Dasar - Maulina Fatmawati; Minsih Minsih (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Curriculum changes after the new normal persuaded the education to adjust the one of policies of the Independent Curriculum (Kurikulum Merdeka) which is the Pancasila Student Profile Program. There is one of the particular characteristics on the Independent Curriculum (Kurikulum Merdeka) namely the Pancasila student profile which is used to intensify character education in Indonesia. The research aims to describe the implementation of the Pancasila Student Profile Program to enhance the creativity of students in Elementary School. A qualitative approach with phenomenological design is chosen as the research method. The techniques to gain the data are interviews, observation, and documentation. This research analyses the activity in the Elementary School Special Program of Muhammadiyah Kottabarat Surakarta which gained the results on the implementation of the Pancasila Student Profile Program on a theme of "Sustainable Lifestyle" (Gaya Hidup Berkelanjutan). This research revealed four steps namely introduction step, contextual, action, and follow-up in implementing the Pancasila Student Profile Program.  In the follow-up steps, in the name of establishing creativity, students must sort the litter, and make a beautiful functional thing from it then, the secondhand litter can be more useful in life.